Understanding China's Overcapacity - Xu, Dianqing (Springer Singapore, 2018)
This book analyzes of the surplus of production capacity in China. According to a government statement, there is a serious surplus of productive capacity in the steel, cement, glass, aluminum, and shipbuilding industries. There was no surplus of productive capacity in above industries between 2002 and 2012, and the current surplus is due to poor government policies on real estate prices after 2012. The book argues that if the Chinese government invested more in social welfare housing over the next few years the surplus of productive capacity would very soon disappear.